Analisis Mekanisme Pembayaran Pajak Kendaraan Bermotor di Kantor Sistem Administrasi Manunggal Satu Atap Kecamatan Kuantan Tengah - Elfi Rahmita Sari; Sarjan M; Emilia Emharis; Rika Ramadhanti; Shilvirichiyanti Shilvirichiyanti (Journal on Education, 2024)
Currently, the administrative procedures for tax collection at the SAMSAT office, most people do not know the mechanism for tax collection carried out by officers. So based on this, the author is interested in researching "The mechanism for paying Motor Vehicle Tax at the One-Stop Manunggal Administration System office, Kuantan Singingi Regency." The type of research uses a qualitative descriptive method. The data collection techniques that the author uses in this research are observation and interviews. Motor vehicle tax is a mandatory contribution that can be imposed on every taxpayer for the objects they own. The aim of this research is to analyze the motor vehicle tax mechanism. The problem with this research is that they don't want to queue for a long time and many people still make payments through other people. It is hoped that the vehicle tax payment mechanism at the Kuantan Singingi Regency One-Stop Single-Stop Administration unit office will remain in accordance with the Presidential Regulation of the Republic of Indonesia Number 5 of 2015 concerning the implementation of the One-Stop Single-Stop Administration System for Motor Vehicles. The data collection method is carried out by means of a questionnaire and documentation. Based on the results of research carried out by researchers, the results were obtained in the quite good category, with an average score of 3.37%.